Coexistence of the Living and the Dead - Azadijou, Reza (2018)
One of the issues that has been discussed by the archaeologists is that of burial rituals and relevant beliefs of various pre-historic societies (early human communities). According to archaeological excavations, various aspects of burial have been analytically studied among which one can refer to such aspects as the position of corps, internal and external structural forms of the graves as well as ideological and cultural aspects.  On the one hand, generalization of the burial tradition and beliefs of primitive societies and applying them to the belief systems of some of the contemporary societies based on their religious perspective of the life after death and on the other hand, inattention to its specific meaning and application, have caused the reader to misunderstand this burial tradition and ritual. Then, the author believes that the existing beliefs and culture regarding death are based on the fear of death as well as the act of dying and the dead person. Burying the dead person’s properties with him/her is one of the manifestations of fear of death phenomenon and act of dying.